[The cost and return of rotational cropping of tomato [Lycopersicon esculentum] with other vegetables in peat soils [Peninsular Malaysia]] - Haron Ashari (Institut Penyelidikan dan Kemajuan Pertanian Malaysia, Pontian, Johor. Bahagian Penyelidikan Tanaman Pelbagai) (2013)
Tomato growers in the peat areas of the Integrated Agricultural Development Project of West Johore, Peninsular Malaysia can rotate their tomato crop with other vegetable types such as cabbage, long bean or French bean. Local Verification Trial results have shown that when tomato was rotated with cabbage, the return per dollar invested was approximately 2.5 times. Similarly, when tomato was rotated with long bean, the return per dollar invested was about 2.0 times and with French bean, the return per dollar invested was about 1.6 times